KARAKTERISTIK EDIBLE FILM DARI PATI GANYONG (Canna edulis Kerr.) BERANTIMIKROBA - Iqbal Syaichurrozi; Netty Handayani; Dyah Hesti Wardhani (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2012)
Edible films are thin layers that can maintain the quality of food products, are edible and environment friendly. Additives such as antimicrobial are added to improve the quality of edible films in handling food product. The purpose of this research is to study the effects of antimicrobial substances of characteristics of edible films from canna starch. The films prepared from 2% w/v of canna starch and 1% v/v (solution basis) of sorbitol. Garlic powder and turmeric powder were used as antimicrobial at 0.01% w/v solution concentration. Moisture content, thickness, the percentage elongation and tensile strength were determined. Antimicrobial testing performed using agar diffusion method and observed for the zone of inhibition growth of E.coli. The results show the control edible film has 18.72% of a moisture content, 0.08 mm of film thickness, 2.75 N/mm2 of tensile strength and 37.78 % percentage of elongation. The addition of the antimicrobial substances decreased the water content, the percentage of elongation and the tensile strength but increased the thickness. Antimicrobial testing showed that the addition of benzoic acid in the film were unable to inhibit the growth of E.coli.